Possibility of application high intensity ultrasound in milk industry - Zoran Herceg; Mladen Brnčić; Anet Režek Jambrak; Suzana Rimac Brnčić; Marija Badanjak; Irma Sokolić (Mljekarstvo)
Recently, a lot of investigations have been focused on development of the novel food processing techniques with the aim to obtain the high quality food products. High intensive ultrasound applied to the milk can destroy some microorganisms and save energy and process time significantly, using milder thermal treatment and obtaining product with higher nutritive value. Therefore, ultrasound treatment has proved to be potentially very successful technique of milk sterilization, particularly in combination with increased temperature.